Capitalistic Transition in Food System and Food consumption in Mae Cham District, Chiang Mai, Thailand - Poon Theingburanathum; Pongtip Thiengburanathum (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
Mae Cham district is located only 156 kilometers from the center for Chiang Mai, but the road trip would take at least 3 hours on the meandering mountains road. The first dirt road that provides access between Mae Cham in Chiang Mai was completed in 1963. The result of the road network and access to the global market has both positive and negative impacts on the people pf Mae Cham. The access to Mae Cham has transformed the food production system in Mae Cham from being self sufficient to becoming a part of the national and international food chain. The crops on the field have changed from rice to cash crops like animal feed corn and from local vegetables to commercial crops like cabbages, to feed into the national and international food chains. The consumption of local food has been transformed as well. The local dishes remain the same, while the added ingredient such as monosodium glutamate, fish sauce, seasoning powders that have increase the chance of high blood pressure, heart disease and diabetes.